Clinton Confidential : The Climb to Power : The Unauthorized Biography of Bill and Hillary Clinton - Carpozi, George (Del Mar, California Emery Dalton Books, 1995)
This book chronicles Bill and Hillary Clinton's ambitious journey, starting with Clinton's youth, through his days as an anti-war protester and draft resister at Georgetown University and Oxford University, to Yale Law school, where he meets his future bride and political partner, Hillary Rodham. Bill Clinton lusted after the presidency at an early age. Every move he made seemed to be part of a cunning strategy to attain his ultimate tenancy of the White House. Starting with his first political gig as Arkansas's attorney general, the reader gets an inside look at Clinton's machinations that become increasingly Machiavellian throughout his five-term career as governor. As Hillary gains powerful influence in her own career, you learn how she secretly struggles to keep her star from outshining her husband's. Clinton Confidential: The Climb to Power is an astonishingly frank analysis of our 42nd president and his wife
Include Illustration and Index
Keywords: Presidents -- Presidents' spouses -- United States -- Clinton, Hillary Rodham